Increased Albumin Oxidation in Cerebrospinal Fluid and Plasma from Alzheimer’s Disease Patients - Montserrat Costa; Raquel Horrillo; Ana María Ortiz; Alba Pérez; Anna Mestre; Agustı́n Ruiz; Merçé Boada; Salvador Grancha (2018)
Oxidative stress in the brain and peripheral systems is considered a major player in Alzheimer's disease (AD). Albumin is the main transporter and the main extracellular antioxidant in the human body.Here we explore for the first time the oxidation status of cerebrospinal fluid (CSF) and plasma albumin in AD in comparison to healthy subjects.Plasma and CSF samples were obtained from mild-moderate AD patients and control healthy age-matched donors. Albumin redox state forms (reduced: HMA; reversibly oxidized: HNA1; irreversibly oxidized: HNA2) were determined by HPLC. Albumin post-translational modifications (PTM) analysis was performed by mass spectrometry.HPLC showed less HMA in AD plasma than in controls (54.1% versus 65.2% ; p < 0.0001), mainly at expense of HNA1 (42.8% versus 32.5% ; p < 0.0001). In AD CSF, HMA was drastically decreased compared to controls (9.6% versus 77.4% ; p < 0.0001), while HNA2 was increased (52.8% versus 7.4% ; p < 0.0001). In AD patients but not in healthy controls, CSF albumin was much more irreversibly oxidized than in plasma (close to 20-fold increase in HNA2). PTM analysis showed that AD CSF albumin samples behave as a differentiated cluster, thus confirming the albumin oxidative pattern observed by HPLC.CSF albumin oxidation in AD patients was dramatically increased comparing to healthy controls, while in plasma this increase was smaller. CSF albumin in AD patients was much more oxidized than in plasma, but this effect was not observed in healthy controls. These results suggest that albumin oxidation, especially in CSF, and its role in AD deserves further investigation.